2008
DOI: 10.1111/j.1525-142x.2008.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression in cotton fibers from wild and domesticated Gossypium barbadense

Abstract: Gossypium barbadense is widely cultivated because of its extra-long staple cotton with superior luster, silkiness and high yield. These economically important traits were selected during initial domestication of an agronomically inferior wild ancestor, followed by millennia of human-mediated selection. To reveal the effects of this history on the cotton fiber transcriptome, we conducted comparative expression profiling on mechanically isolated fiber cells at three different stages encompassing early, mid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 91 publications
4
67
0
1
Order By: Relevance
“…Aulah and Malhi [15,16] reported that the absorption of N, in the form of NH 4 + , is not affected by K and that the interaction between N and K is the second most important factor after NPK for increasing crop yield, which is not further increased by the increasing concentrations of N and P without the addition of K. Deng et al [13] suggested that several metabolic activities of ramie are affected by N, P, or K deficiency. For instance, the expression of profilin is down regulated under P-deficient conditions, and this affects fiber synthesis [13,17]. Fiber fresh and dry weights were also increased by fertilizer application, particularly NPK, which is consistent with the results reported by Liu et al [18].…”
Section: Discussionsupporting
confidence: 82%
“…Aulah and Malhi [15,16] reported that the absorption of N, in the form of NH 4 + , is not affected by K and that the interaction between N and K is the second most important factor after NPK for increasing crop yield, which is not further increased by the increasing concentrations of N and P without the addition of K. Deng et al [13] suggested that several metabolic activities of ramie are affected by N, P, or K deficiency. For instance, the expression of profilin is down regulated under P-deficient conditions, and this affects fiber synthesis [13,17]. Fiber fresh and dry weights were also increased by fertilizer application, particularly NPK, which is consistent with the results reported by Liu et al [18].…”
Section: Discussionsupporting
confidence: 82%
“…As a specialized unicellular trichome with a greatly exaggerated length, cotton fiber represents a masterpiece of human domestication, made all the more remarkable by its parallel, independent origin in four cultivated species (three studied here). Little is known about the genetic, genomic, or metabolomic transformations that mediate these independent transformations, although insights are emerging from comparative expression profiling experiments (3)(4)(5)(6). The present study sheds light on one aspect of this general question, implicating the up-regulation of the profilin gene family concomitant with strong directional selection under human domestication.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to the former, analyses of fiber growth curves reveal that cotton domestication at both the diploid and allopolyploid levels is associated with a prolonged period of fiber elongation (2). As to the genomic underpinnings of fiber evolution, a number of recent studies are generating insights and a rich data set based on comparative transcriptome profiling of fiber development in wild vs. domesticated cotton (3)(4)(5)(6), and from ongoing comparative proteomic analyses (7). Rapp et al (2010), for example, reported thousands of genes that are differentially expressed in developing fiber between wild and domesticated G. hirsutum, many associated with key developmental processes presumed to play important roles in primary and secondary wall synthesis and in modulation of reactive oxygen species (3,5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the change in gene expression during cotton fiber initiation and development, and some genes have been studied for their functions during cotton fiber development (Asif et al 2008;Chaudhary et al 2008Chaudhary et al , 2009FeiFei et al 2009;Gao et al 2007;Gou et al 2007;He et al 2008;Hovav et al 2008;Huang et al 2008a, b;Iqbal et al 2008;Li et al 2003Li et al , 2005aLiu et al 2009;Michailidis et al 2009;Schwartz and Smith 2008;Taliercio and Boykin 2007;Tu et al 2007;Wu et al 2008;Xu et al 2008). However, the mechanism of controlling cotton fiber differentiation and development is still unknown.…”
Section: Introductionmentioning
confidence: 98%